An Injectable Strong Hydrogel for Bone Reconstruction. Issue 17 (28th July 2019) - Zhao, Yanran; Cui, Zhiyong; Liu, Bingchuan; Xiang, Junfeng; Qiu, Dong; Tian, Yun; Qu, Xiaozhong; Yang, Zhenzhong
Abstract: For treating bone defects in periarticular fractures, there is a lack of biomaterial with injectable characteristics, tough structure, and osteogenic capacity for providing a whole‐structure support and osteogenesis in the defect area. An injectable hydrogel is an ideal implant, however is weak as load‐bearing scaffolds. Herein, a new strategy, i.e., an in situ formation of "active" composite double network (DN), is raised for the preparation of an injectable strong hydrogel particularly against compression. As a demonstration, 4‐carboxyphenylboronic acid grafted poly(vinyl alcohol) (PVA) is crosslinked using calcium ions to provide a tough frame while bioactive glass (BG) microspheres are associated by poly(ethylene glycol) to obtain an interpenetrated inorganic network for reinforcement. The injected PVA/BG DN hydrogel gains compressive strength, modulus, and fracture energy of 34 MPa, 0.8 MPa, and 40 kJ m −2, respectively. Then, the properties can be "autostrengthened" to 57 MPa, 2 MPa, and 65 kJ m −2 by mineralization in 14 days. In vivo experiments prove that the injected DN hydrogel is more efficient to treat femoral supracondylar bone defects than the implanted bulk DN gel. The work suggests a facile way to obtain a strong hydrogel with injectability, cytocompatibility, and tailorable functionality. Abstract : An injectable strong hydrogel, with a composite double‐network structure and autostrengthening performance, is developed, showing ideal compressive properties, biocompatibility, and osteogenic activity for application as an injectable load‐bearing scaffold to treat periarticular bone defect.